IMPACTO DE FATORES PSICOSSOCIAIS SOBRE O DESEMPENHO: UM ESTUDO COM TUTORES EM EAD - Cintra, Josiane (2015)
Taking into consideration the fast expansion of distance education (DE) in Brazil, and the challenges it still faces, it is important to take a careful look at the issues involved in it. From the viewpoint of Psychology, the focus on the individual working with DE is fundamental. In this context, the tutor s work stands out; it is an outline of this complex world of working in DE, target of this study. The tutor s professional performance depends on technological, environmental, and psychosocial factors. This study aimed to check out the impact that such beliefs as self-efficacy at work, social support perception, and engagement at work have on the performance of tutors for disciplines offered at a distance. The research had a transversal character, and it was developed at a Brazilian university based in São Paulo. 227 tutors participated, 62por cento female, 65por cento married, 66por cento aged between 25 and 45 years old, and 97por cento with post-graduation. Data collection was carried out electronically; valid and reliable scales of self-efficacy, engagement, and social support perception at work were applied, besides a socialdemographic questionnaire. Institutional information was surveyed about performance. Statistical descriptive analyses revealed that more than 75por cento of them realize they have enough and important information as well as reliable and affective relationships at work, whereas half of them realize that have good material, financial, technical, and managerial inputs. Results of variance analyses (ANOVA) revealed that there were no differences between the performance of groups that exercise other professional activities besides tutoring and those who do not, nor among groups that have or do not have specific formation to act in tutoring in DE. Results of multiple linear regressions revealed that beliefs in self-efficacy at work, social support perception, and engagement at work do not explain the performance variance among tutors. The results were discussed, chiefly backed up in the small variability of the performance marks, taking into consideration that 98.8por cento of the tutors obtained higher than the average score of the assessment tool used by the institution, which may reveal difficulties in the evaluation process or problems with the instruments validity. In addition, questions were discussed concerning human performance as a complex, multidimensional phenomenon, seeking to approach the role of the study variables in its determination, in the light of the specillized literature. Finally, methodological, theoretical, and practical implications were presented, as well as limitations to the study and research agenda.